Strategi Humas Dalam Mempromosikan SMK Darussalam Blokagung Banyuwangi Tahun Pembelajaran 2018/2019 - Kholiq, Ilham Nur; Khoiri, Muhammad Shirotun (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2019)
The focus of this research is the strategy used by WKS. Public Relations SMK Darussalam to attract participation and provide understanding to the public that SMK Darussalam Blockagung in the current era of globalization. This research approach uses qualitative and descriptive types. Data collection techniques using a) observation, b) interview, c) documentation. While the analysis of the data used by researchers is 1) Data collection, 2) Data reduction, 3) Presentation of data, 4) Withdrawal of Conclusions / Verification, For the validity of the data using source data collection. The conclusion of this study is based on the results of the analysis of the findings in the field that 1) Promotion strategies carried out by WKS. public relations SMK Darussalam by distributing brochures, banners, then publications and socialization to the public, 2) WKS. Humans and its team have carried out their task quite effectively by evaluating activities that have not yet been carried out how the future solutions so that SMK Darussalam Blokagung can be better known by the public, 3) Factors that support the program activities include the establishment of harmonious communication between internal parties (all school members) with external parties (public or community) on the other hand the factors that hampered the promotion process of SMK Darussalam institutions include the lack of budget funds needed in the process of promoting institutions, human resources (HR) who are still young so there is still lack of experience.